Deficit irrigation and nitrogen rate effects on growth, yield, tuber quality and petiole nutrient dynamics in four potato cultivars grown in San Luis Valley, Colorado - Barka, Abdulssamad, author; Essah, Samuel Y. C., advisor; Davis, Jessica G., advisor; Andales, Allan, committee member; Qian, Yaling, committee member (Colorado State University. Libraries, 2025)
Potato (Solanum tuberosum L.) production in Colorado's San Luis Valley (SLV) is challenged by limited water availability, rising input costs, and environmental concerns related to fertilizer use, making efficient irrigation and nitrogen (N) management essential. This dissertation integrates three coordinated field studies conducted over two seasons (2016–2017) to evaluate how deficit irrigation and reduced N application affect yield, tuber quality, water- and nitrogen-use efficiency, and petiole nutrient dynamics in four cultivars (Canela Russet, Mesa Russet, Russet Norkotah 3, and Yukon Gold). Field experiments applied three irrigation levels (~70%, 80%, and 100%) evapotranspiration (ET) replacement, initiated post-bulking at ~60 days after planting, DAP) and two seasonal N rates (165 vs. 131 kg N ha-1, split-applied). Measurements included yield components, leaf area index (LAI), tuber bulking (TB), tuber quality traits [specific gravity (SG), starch content (SC), tuber dry matter (TDM)], water- and nitrogen-use efficiencies (WUE, NUE), and petiole nutrients (NO3-N P, PO4-P, K, Ca, Mg, S and Na) sampled at ~50, 60, 70, and 90 DAP. Data was analyzed using linear mixed models and correlation analyses. Results showed that moderate deficit irrigation initiated after the onset of tuber bulking (≤18% ET reduction) maintained yields in Canela Russet, Mesa Russet, and Yukon Gold, but reduced yield in Russet Norkotah 3. Severe deficits irrigation decreased yield and quality across cultivars, whereas moderate deficits often enhanced or maintained SG, SC, and TDM. Reducing seasonal N to 131 kg ha-1 consistently improved NUE without compromising yield or quality, while WUE responses varied by cultivar and season. Growth stages strongly governed petiole nutrient dynamics, with early-peaking nutrients (NO3-N, P, PO4-P, K, and S) and late-accumulating nutrients (Ca, Mg, and Na) forming clearly separated, negatively correlated clusters. LAI near peak canopy (80-100 DAP) and TB (~110-115 DAP) were reliable predictors of final yield. Importantly, extrapolating these findings to the ~20,234 ha of potato land in the SLV suggests that adopting moderate irrigation savings in tolerant cultivars could conserve ~17.2 million m3 (~850 m3/ha) of water annually, while reduced N rates could save ~688,000 kg (~ 34 kg N/ha) of fertilizer annually across ~20,234 ha. These reductions will lower production costs and reduce nitrate leaching and groundwater contamination, protecting drinking water quality and community health. In conclusion, these studies support a cultivar- and stage-aware management framework: implement moderate irrigation savings after the onset of tuber bulking only in tolerant cultivars, standardize N near 131 kg ha-1 in split applications, and guide in-season decisions using LAI, TB, and stage-targeted petiole diagnostics. This integrated approach enables water conservation and enhanced NUE while sustaining yield and quality in an aquifer-constrained production system.
Keywords: Solanum tuberosum; deficit irrigation; nitrogen management; growth stage; yield; tuber quality; water and nitrogen use efficiency; petiole nutrients